Continuous Training Strategy to improve office skills in Communication Teachers, UNAN-Managua - Jaime-Manzanarez, Bryan Alexander (Scientific journal of social studies, 2025)
This scientific article presents the application of a teacher training strategy designed to improve the office skills of teachers in the Communication for Development program at the National Autonomous University of Nicaragua, Managua (UNAN-Managua). The study was carried out using a quasi-experimental pretest-posttest design with a mixed approach, combining quantitative and qualitative methods to evaluate the impact of the intervention. Data were collected through structured surveys, direct observation, and performance analysis before and after training. The results showed significant improvements in the use of technological tools such as Office 365 and institutional platforms, optimizing the academic and administrative management of teachers. For the application of this training strategy, the Competency-Based Learning (CBL) model was used, which allowed participants to strengthen fundamental skills to perform their functions more efficiently in a digital environment. The quantitative data analysis reflected an increase in the mastery of digital tools, while the qualitative findings showed greater confidence and autonomy in the integration of technology into teaching practice. The training also contributed to improving institutional planning and the professional development of teachers, aligning with the National Education Strategy “Blessings and Victories” 2024-2026, promoted by the Government of Reconciliation and National Unity.